Geographical structure of genetic diversity in Loudetia simplex (Poaceae) in Madagascar and South Africa - (:unkn) unknown (My University, 2021)
Abstract Ecologically dominant species are primary determinants of ecosystem function, especially in grassy ecosystems, but the history and biology of grassy ecosystems in Madagascar are poorly understood compared to those of Africa. Loudetia simplex is a C4 perennial grass that is adapted to fire and common to dominant across Africa. It is also widespread across central Madagascar in what are often thought to be human-derived grasslands, leading us to question how recently L. simplex arrived and how it spread across Madagascar. To address this, we collected population genetic data for 11 nuclear and 11 plastid microsatellite loci, newly developed for this study, for > 200 accessions from 78 populations of L. simplex, primarily from Madagascar and South Africa. Malagasy and African populations are genetically differentiated and harbour distinct plastid lineages. We demonstrate distinct geographically clustered diploid, tetraploid and hexaploid groups. The Malagasy hexaploid populations cluster into northern and southern types. In South Africa, diploid populations in the Drakensberg are distinct from tetraploid populations in north-eastern South Africa. Different genetic clusters are associated with significantly different precipitation and temperature. We conclude that L. simplex is native to both Madagascar and South Africa, probably with a single colonization event from Africa to Madagascar followed by pre-human diversification of L. simplex populations in Madagascar.
Keywords: African Research